Associação entre hábitos bucais de sucção não nutritivos e as relações oclusais ântero-posteriores na dentição decídua, em nipo-brasileiros - Ito, Carla (2006)
The aim this study was to evaluate the association between digital and/or pacifier sucking habits and the anteroposterior occlusal relationships in Japanese-Brazilian children in the deciduous dentition. A previously-calibrated dentist carried out clinical examination in 410 children (206 males and 204 females), aged 2–6 years, enrolled in private preschools in the state of São Paulo. Questionnaires concerning non-nutritive sucking habits were sent to their parents. Chi-square test (p<0.05) was used to evaluate the association between sucking habits and anteroposterior malocclusions (increased overjet, Class II canine relationship and distal step molar relationship). Logistic regression test was used to determine relative risks (odds ratio) for these malocclusions. The prevalence observed for non-nutritive sucking habits, increased overjet, Class II canine relationship and distal step molar relationship was 44.6%, 16.6%, 8.9%, and 6%, respectively. Results showed that children with digital and/or pacifier-sucking habits had a higher prevalence of increased overjet, Class II canine relationship and distal step molar relationship, with a two-fold higher risk when compared to children without such habits. However, these unfavorable repercussions were observed only for children having persistent habits between 2 and 4 years of age. Besides, these prevalences were also high for children with such habits observed at the time of clinical examination or even interrupted in the last six months. It was observed a reduction in the prevalence of anteroposterior occlusal alterations when the habits were interrupted in a period longer than six months.